Enhancing Interoceptive Abilities and Emotional Processing: Effects of HD-tDCS - Jasmin Schultze; Sara A. Hajian; Sandra Mai-Lippold; Olga Pollatos (Journal of Integrative Neuroscience, 2024)
Background: Interoception, the processing and integration of bodily signals, is crucial for emotional experiences and overall well-being. The interoceptive network, including the somatosensory cortices, has been recognized for its role in interoceptive and emotional processing. High-definition transcranial, direct-current stimulation (HD-tDCS) has been demonstrated to modulate brain activity in the primary somatosensory cortex (S1). Based on those findings, we hypothesized that anodal HD-tDCS over the right S1 would enhance interoceptive abilities and heighten emotional perception. Methods: Thirty-six healthy adults participated in two sessions separated by at least one week. A 20-min HD-tDCS stimulation (2 mA), and a sham stimulation, were applied in randomized order. Both conditions involved pre-tDCS physical activation by ergometer cycling. Interoceptive abilities were assessed before and after both sessions using a heartbeat-perception and respiratory-load task. Emotional perception was measured using four matched international affective picture system (IAPS) picture sets presented randomly. Results: Active HD-tDCS did not significantly improve interoceptive accuracy, interoceptive emotion evaluation, or interoceptive sensibility. However, a notable increase in cardiac interoceptive awareness was observed after active HD-tDCS. The expected enhancement of emotional processing was not observed. Conclusions: This study represents the first attempt to modulate interoceptive and emotional processing using HD-tDCS over S1. Although consistent enhancement was not observed, our findings provide insights into the modulation of interoceptive and emotional processes with HD-tDCS, suggesting avenues for further research. Further studies should consider the nuanced effects of stimulation techniques and the complex interplay between interoception and emotion.